A note on partition functions of Gepner model orientifolds - Blumenhagen, Ralph; Weigand, Timo (Physics letters, 2004)
In this note we generalize the description of simple current extended Gepner model orientifolds as presented in hep-th/0401148 on the case of even levels and non-trivial dressings of the parity transformation. We provide a comprehensive list of all the important ingredients for the construction of such orientifolds. Namely we present explicit expressions for the Klein-bottle, annulus and Möbius strip amplitudes and derive the general tadpole cancellation conditions. As an example we construct a supersymmetric Pati-Salam like model.